Holothuria (Selenkothuria) parvispinea n. sp. (Echinodermata, Hololthuroidea, Holothuriidae) with key to the sub-genus Selenkothuria - Massin, Claude (Zootaxa, 2013)
Description of a new species from Australia, belonging to the subgenus Selenkothuria (Holothuria, Aspidochirotida). A dichotomous key of the thirteen valid species included in the subgenus is also given. The species H. perrieri Thandar, 1977 and H. spinea Cherbonnier, 1988 are considered as non valid.